Factor Analysis of Service Performance in Higher Education Institutions - Endah Sundaning Kinanti; Hamzah Ritchi; Sofik Handoyo (Universitas Padjadjaran, 2020)
This research aims to examine the determinants of service performance in higher education institutions on student perceptions. This research uses Exploratory Factor Analysis (EFA) in determining the factors. The construct is built based on the literature on service performance and higher education. Data were collected using a questionnaire to a state university with legal entity students in Bandung. The results indicate that there are seven determinants of service performance, namely reliability, assurance, tangibles, responsiveness, access, and reputation. The total variance of these factors is 65.7 percent, which means that the seven factors determine 65.7 % of service performance in higher education in Indonesia, and 34.3% is defined by other factors that are not examined in this research. The results of this study contribute to the literature on service performance factors in higher education in Indonesia. The factors can be used as a reference by higher education institutions to improve service quality in all aspects